Aqueous solubilization of C(60) fullerene by natural protein surfactants, latherin and ranaspumin-2 - Vance, Steven J. (Biophys Chem, 2016)
C(60) fullerene is not soluble in water and dispersion usually requires organic solvents, sonication or vigorous mechanical mixing. However, we show here that mixing of pristine C(60) in water with natural surfactant proteins latherin and ranaspumin-2 (Rsn-2) at low concentrations yields stable aqueous dispersions with spectroscopic properties similar to those previously obtained by more vigorous methods. Particle sizes are significantly smaller than those achieved by mechanical dispersion alone, and concentrations are compatible with clusters approximating 1:1 protein:C(60) stoichiometry. These proteins can also be adsorbed onto more intractable carbon nanotubes. This promises to be a convenient way to interface a range of hydrophobic nanoparticles and related materials with biological macromolecules, with potential to exploit the versatility of recombinant protein engineering in the development of nano-bio interface devices. It also has potential consequences for toxicological aspects of these and similar nanoparticles.